Comparison of Hematological Phenotypes of COPD Exacerbations in Hospitalized Patients after Emergency Department Admission - Emre Şancı; Asım Enes Özbek; Furkan Alkan; Hikmet Kılınç; Hüseyin Cahit Halhallı (İstanbul Medical Journal, 2023)

(untitled)
Introduction:The aging of the communities and higher pollution levels increases chronic obstructive pulmonary disease (COPD) burden and are projected to rise in the number of the patients with COPD and its exacerbations. There is little evidence for short-term outcomes of COPD exacerbations of the biomarkers that are easily available. Biomarker-based hematological phenotype classification is useful and effective for outcome predictions. This study evaluates the relationship between the phenotypes of patients with COPD who presented in the emergency department due to COPD exacerbation and admitted to the hospital have been evaluated.Methods:All hospitalized patients older than 18 years old who presented to the emergency department due to the COPD exacerbation between July 2018 and July 2020 were included in the study. The patient data evaluated retrospectively for vital parameters, biomarker results, and mortality rates. The primary outcome measure of the study was determined as the thirty-day mortality rates of the groups. Secondary outcome measures were determined by comparing the differences between the trophilic and eosinophilic groups.Results:One hundred forty-three patients were included in the study. The mean age of the patients was 74.8±10.6. One hundred and two of the patients (71.3%) were male. The neutrophilic and eosinophilic groups had a statistically significant difference in body temperature and heart rate (p=0.018 and p=0.001, respectively). In contrast, no significant difference was observed for systolic blood pressure, diastolic blood pressure, and sPO2 (p=0.400, p=0.564, p=0.248, respectively). One month mortality of the neutrophilic and eosinophilic groups were 15.9% and 3.2%, respectively. Blood neutrophil count levels have been assigned in 3 different groups for mortality and compared which had no significant difference for 1,3 and 12-month mortality (p=0.142, 0.280, 0.351 respectively).Conclusion:The patients admitted to the hospital via the emergency department had no mortality difference between different neutrophil levels or hematologic phenotypes. Further studies are required to assess cutoff values of blood neutrophil counts as an independent biomarker.